Between Stress and Tone Conference (BeST), 16-18 June 2005, in Leiden, The Netherlands - Pletikos Olof, Elenmari (Array, 2005)
The oldest university in the Netherlands in the city of Leiden hosted a conference entitled “ Between Stress and Tone” (BeST) from 16 until 18 June, 2005. A wide area of research where various phonetic and phonological typologies of prosodic systems come together with the description and research of production, perception and function of stress and accent in particular languages.